Exercise training normalizes ACE and ACE2 in the brain of rabbits with pacing-induced heart failure - Kar, Sumit (American Physiological Society, 2010)
Exercise training (EX) normalizes sympathetic outflow and plasma ANG II in chronic heart failure (CHF). The central mechanisms by which EX reduces this sympathoexcitatory state are unclear, but EX may alter components of the brain renin-angiotensin system (RAS). Angiotensin-converting enzyme (ACE) may mediate an increase in sympathetic nerve activity (SNA). ACE2 metabolizes ANG II to ANG-(1–7), which may have antagonistic effects to ANG II. Little is known concerning the regulation of ACE and ACE2 in the brain and the effect of EX on these enzymes, especially in the CHF state. This study aimed to investigate the effects of EX on the regulation of ACE and ACE2 in the brain in an animal model of CHF. We hypothesized that the ratio of ACE to ACE2 would increase in CHF and would be reduced by EX. Experiments were performed on New Zealand White rabbits divided into the following groups: sham, sham + EX, CHF, and CHF + EX (n = 5 rabbits/group). The cortex, cerebellum, medulla, hypothalamus, paraventricular nucleus (PVN), nucleus tractus solitarii (NTS), and rostral ventrolateral medulla (RVLM) were analyzed. ACE protein and mRNA expression in the cerebellum, medulla, hypothalamus, PVN, NTS, and RVLM were significantly upregulated in CHF rabbits (ratio of ACE to GAPDH: 0.3 ± 0.03 to 0.8 ± 0.10 in the RVLM, P < 0.05). EX normalized this upregulation compared with CHF (0.8 ± 0.1 to 0.4 ± 0.1 in the RVLM). ACE2 protein and mRNA expression decreased in CHF (ratio of ACE2 to GAPDH: 0.3 ± 0.02 to 0.1 ± 0.01 in the RVLM). EX increased ACE2 expression compared with CHF (0.1 ± 0.01 to 0.8 ± 0.1 in the RVLM). ACE2 was present in the cytoplasm of neurons and ACE in endothelial cells. These data suggest that the activation of the central RAS in animals with CHF involves an imbalance of ACE and ACE2 in regions of the brain that regulate autonomic function and that EX can reverse this imbalance.